Improving surface and mechanical properties of alginate films by using ethanol as a co-solvent during external gelation. (5th June 2015) - Li, Jiwei; He, Jinmei; Huang, Yudong; Li, Dalong; Chen, Xiaotong
Highlights: This work provides a new method to improve the external gelation technique. Adding ethanol improved the visual appearance of alginate films. Adding ethanol could reduce the surface roughness of alginate films. Adding ethanol improved the mechanical properties of alginate films. Extent of crosslinking depended on ethanol content. Abstract: Alginate films were prepared by solution casting method and further ionically crosslinked in a calcium chloride (CaCl2 ) water solution containing different proportions (0–40% v/v) of ethanol as the co-solvent. The addition of ethanol into the CaCl2 water solution was found to improve the visual appearance, thickness, surface homogeneity, and mechanical properties of the films, which can be attributed to the reduced swelling degree of films during crosslinking process. Furthermore, Fourier transform infrared spectroscopy (FTIR) and energy dispersive spectroscopy (EDS) analysis indicated that the incorporation of ethanol into the crosslinking solution did not detract from the uniformity of crosslinking throughout the film matrix. However, the swelling degree and calcium content determination indicated that the Ca 2+ crosslinking degree decreased when the ethanol proportion exceeded 30% v/v. Consequently, this study introduces a green, efficient, and simple technique for the preparation of calcium alginate films with excellent surface appearance and mechanical properties for pharmaceutical products.